Hemifacial spasm in a patient with basilar artery dolichoectasia caused by uncontrolled hypertension. Issue 5 (1st January 2016) - Crabtree, Gordon S.; Gish, David; Goldberg, David
Abstract : A 47-year-old male presented with a 2-year history of hemifacial spasm. Magnetic resonance imaging performed showed his tortuous basilar artery with nerve compression, and the patient was treated conservatively with botulinum toxin injections with complete resolution of symptoms. This rare disease was caused by his long history of hypertension, which led to his major basilar artery dolichoectasia.